Synthesis and properties of three guanidinium salts based on high-oxygen-balanced 1, 4-dinitramino-3, 5-dinitropyrazolate anion. (1st May 2021) - Li, Guanglei; Huang, Haifeng; Yang, Jun; Yan, Chao; Li, Wei; Duan, Hongzhen
Graphical abstract: A series of new energetic salts have been synthesized by combining cations with high oxygen balance and different high hydrogen content anions. These new energetic salts is fully characterized by IR, NMR, TG-DSC, elemental analysis, single-crystal X-ray diffraction and sensitivity test. They are potentially high-energy materials that can be used as primary explosives. Abstract: Three guanidinium salts based on high-oxygen-balanced 1, 4-dinitramino-3, 5-dinitropyrazolate anion were synthesized. And the structures of these salts were characterized by NMR ( 1 H and 13 C), IR spectroscopy, and elemental analysis, and single crystal X-ray diffraction. Furthermore, their thermal stabilities were analyzed by differential scanning calorimetric measurements (DSC). Their enthalpies of formation were calculated based on isomesdic reaction by using Gaussian 09 program to be between 193.4 and 613.2 kJ mol −1 . The results show that the densities of salts 8 –10 are between 1.572 and 1.693 g·cm −3, and their thermal decomposition temperatures are between 93.4 and 175.7 ℃. Their detonation velocities and detonation pressures are calculated according to Kamlet-Jacobs detonation equations to be between 7638 and 8227 m s −1 and 23.8–28.8 GPa, respectively. Salts 9 and 10 have better detonation performance and high sensitivity, and can be used as primary explosives.